Plasma splashing from Al and Cu materials induced by and Nd : YAG pulsed laser - Bidin, Noriah; Qindeel, R.; Daud, M. Y.; Bhatti, K. A. (MAIK Nauka / Interperiodica, 2007)
Plasma splashing from Al and Cu target materials and the growth of thin films on Cu and Al, respectively, has been studied using a Q-switched Nd:YAG laser with a 1064-nm, 80-mJ, 8-ns pulse width as the source of ablation. The target kept rotating and the substrate, Cu for Al and vice versa, was placed at an angle of 15Â° with respect to the beam axis. During the laser-matter interaction, the targets absorbed thermal energy within the thermal region depth of 4.7 (1.1) nm, yielding an ablated skin depth of 6.7 (4.2) nm. The surface morphology of the exposed targets was studied by analyzing SEM micrographs obtained using a ZEISS SUPRA 35 VP. The obtained results are explained on the basis of different sputtering/ablation mechanisms. Comparatively severe damage forming a bigger crater is seen on the Al target surface in contrast to the crater on the Cu surface. This observation is correlated with the blustering effect and/or debris formation. Energy dispersive spectroscopy (EDX) of the substrates yielded the deposition of micrometric grain-size particles